Surface modification of electrospun polycaprolactone fibers and effect on cell proliferation. Issue 1 (March 2014) - Arabi, Ahmad; Boggs, Emily; Patel, Manan R.; Zwiesler-Vollick, Julie; Maerz, Tristan; Baker, Kevin; Tuck, Samuel; Corey, Joseph; Li, Yawen
Abstract : Surface modification is an essential tool in tissue engineering using synthetic biomaterial scaffolds. The authors report in this study a simple approach to modify the surface hydrophobicity, roughness and chemistry of electrospun polycaprolactone (PCL) fibers using a combination of oxygen plasma treatment, sodium hydroxide treatment and arginine–glycine–aspartic acid (RGD) immobilization. The modified surfaces were characterized using scanning electron microscopy, atomic force microscopy, water contact angle measurement and X-ray photoelectron spectroscopy (XPS). Plasma treatment decreased the water contact angle. Sodium hydroxide treatment further improved the hydrophilicity and increased the surface roughness. XPS analysis confirmed the presence of amide bonds on RGD-treated fibers. The enhancement of proliferation of ligament fibroblasts within 1 week of culturing on both the plasma- and sodium hydroxide–treated fibers was most likely due to improved wettability by the oxygen plasma treatment. The alignment and penetration of cells on PCL fibers suggested that these materials could be potential scaffold materials for the regeneration of fibrous tissues.